2022
DOI: 10.1111/apt.16763
|View full text |Cite
|
Sign up to set email alerts
|

Liver‐related and extrahepatic events in patients with non‐alcoholic fatty liver disease: a retrospective competing risks analysis

Abstract: Summary Background & Aim Non‐alcoholic fatty liver disease (NAFLD), and especially fibrotic non‐alcoholic steatohepatitis, is associated with high risks of liver‐related events (LRE) and extrahepatic events (EHE). We evaluated the competitive risk occurrence of LRE and EHE in a large cohort of biopsy‐proven NAFLD stratified according to baseline severity of fibrosis. Methods Two thousand one hundred thirty‐five patients with biopsy‐proven NAFLD were enrolled. Observed cumulative incidence functions (CIFs) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 40 publications
2
21
0
1
Order By: Relevance
“…In a meta-analysis of 36 prospective studies, which included more than 5.8 million participants, the risk of fatal or nonfatal cardiovascular events significantly increased in accordance with the increasing severity of fibrosis [ 15 ]. A series of more recent studies have also confirmed the dose-dependent effects of liver fibrosis on the development of cardiovascular and other extrahepatic adverse events [ 16 , 17 ]. Thus, it is perhaps the assessment of liver fibrosis that may make it the most important tool in the assessment of cardiovascular risks in patients with NAFLD and other categories of patients.…”
Section: Introductionmentioning
confidence: 94%
“…In a meta-analysis of 36 prospective studies, which included more than 5.8 million participants, the risk of fatal or nonfatal cardiovascular events significantly increased in accordance with the increasing severity of fibrosis [ 15 ]. A series of more recent studies have also confirmed the dose-dependent effects of liver fibrosis on the development of cardiovascular and other extrahepatic adverse events [ 16 , 17 ]. Thus, it is perhaps the assessment of liver fibrosis that may make it the most important tool in the assessment of cardiovascular risks in patients with NAFLD and other categories of patients.…”
Section: Introductionmentioning
confidence: 94%
“…[OSAS] and chronic obstructive pulmonary disease diabetes [COPD]), osteoporosis, osteopenia and sarcopenia, obesity, and extrahepatic cancers. [20][21][22] This NAFLD heterogeneity has led to the increasing acceptance that NAFLD patients need a more personalized approach probably by the use of molecular tools (-omics approaches, genetic testing), liver fibrosis biomarkers, advanced imaging techniques, and detailed evaluation of each patient's clinical features. 23 NAFLD has been proven a sexual dimorphic disease, with women having a lower risk of developing NAFLD than men and fertile age of women being associated with more severe hepatocyte injury and inflammation but with a lower risk of liver fibrosis than men.…”
Section: Genetic Hormonal Environmental Dietary Factors and Human Naf...mentioning
confidence: 99%
“…Indeed, the heterogeneous spectrum of NAFLD manifestations, spanning from hepatic to extra‐hepatic has been increasingly emerging in recent years. While the most frequent hepatic complications are well characterized, 20,21 the extra‐hepatic complications list is expanding continuously, including cardiovascular events, endocrine disorders, respiratory disorders (obstructive sleep apnea syndrome [OSAS] and chronic obstructive pulmonary disease diabetes [COPD]), osteoporosis, osteopenia and sarcopenia, obesity, and extrahepatic cancers 20–22 23 .…”
Section: Genetic Hormonal Environmental Dietary Factors and Human Naf...mentioning
confidence: 99%
“…Of note, the study supports the notion that raised GGT values may be a marker of sedentary behavior. Therefore, the recent attempts to introduce GGT as a parameter for stratifying dysmetabolic patients may improve our personalized medicine approach to metabolic disorders and NAFLD [51][52][53] .…”
Section: Ggt Metabolic Syndrome Nafld and Fibrosismentioning
confidence: 99%